Rapid Changes In Society, Technology ,Economy And Public Service Institutions (Economic and Bussiness Faculty, Dr Soetomo University, 2017)
Current paper has the purpose to analyze the statement by Drucker (1985) that rapid changes in today’s society, technology, and economy in general are simultaneously a great threat to public-service institutions and even greater opportunity. The statement by Drucker will be analyzed particularly with context of post offices that what are they going through these days or have gone through. Finally, some recommendations will be made for USPS based on the findings of the analysis..